Pengembangan Keterampilan Kreatif Mahasiswa Melalui Pembuatan Gantungan Kunci Clay Beraroma Vanili - Anggit Dyah Kusumastuti; Locita Dara Rasendriya (Jurnal Kabar Masyarakat, 2025)
This activity is intended to improve students' creativity skills and instill an entrepreneurial spirit in 4th semester Business Administration students through training in making key chains from vanilla-scented clay. The implementation method uses a prescientific approach and practice-based learning with 4 main stages, namely planning, implementation, evaluation, and documentation. The results of the training showed a significant increase in six main aspects, namely satisfaction of learning effectiveness involvement, knowledge about clay, technical skills, understanding of entrepreneurship, and student creativity. In addition, this activity forms a collaborative culture, increases self-confidence, and fosters awareness of the potential for independent businesses. These findings indicate that the real practice approach is very effective in encouraging social transformation and the development of students' entrepreneurial character.